Educational Psychology Between Certitudes and Uncertainties - Trif, Victori?a (IntechOpen, 2019)
The title of the book Educational Psychology - Between Certitudes and Uncertainties is relevant for the dynamic and low predictable research from genetics, neurosciences, technologies, etc. that produce challenges and exchanges across sciences. This new framework argues that this book is to be considered a fairly unique and realistic way to rebuild the incongruities and paradoxes in this area. Naturally, "certitudes and uncertainties" is a common denominator for the existing sophisticated academic conventions and for the immense potential of continuous professional development. The title of the book reflects the state of the art, a new trend in the conceptual fabric of educational psychology, and an attitude toward an academic market in the age of many battles in the world of science.